Developmental lung anomalies in adults: A pictorial review. (August 2019) - Cherian, Sujith V.; Kumar, Anupam; Ocazionez, Daniel; Estrada -Y- Martin, Rosa M.; Restrepo, Carlos Santiago
Abstract: Developmental lung anomalies represent a heterogeneous group of diverse, yet related abnormalities that involve the lung parenchyma, pulmonary vasculature or a combination of both-which usually present prenatally and in early childhood. However, a substantial number of cases go unnoticed during childhood and present either incidentally or with recurrent respiratory infections progressing into adulthood. Defective development of the tracheobronchial tree and the pulmonary vasculature are proposed to cause these developmental anomalies. Encountering these lung anomalies in adults is a diagnostic challenge given their rarity and they are often mistaken as other serious pathological conditions, resulting in unnecessary diagnostic tests and procedures. The developmental lung anomalies in adults can be broadly divided into three categories: bronchopulmonary anomalies encompassing congenital bronchial atresia, bronchogenic cysts, congenital lobar emphysema and congenital pulmonary airway malformations. Vascular anomalies include pulmonary agenesis-aplasia- hypoplasia complex, unilateral absence of the pulmonary artery, pulmonary artery sling, partial anomalous pulmonary venous return, pulmonary venous varix and pulmonary arteriovenous malformations. Finally combined lung parenchymal-vascular anomalies of the lung involve hypogenetic lung (scimitar) syndrome and bronchopulmonary sequestration. This article discusses the spectrum of these developmental anomalies of the lung, their etiopathogenesis, clinical and radiographic presentations in adults and management in brief. Highlights: DLAs are rare and frequently misdiagnosed, and diagnosis requires a high index of suspicion. DLAs are broadly divided into bronchopulmonary, vascular and combined lung parenchymal-vascular anomalies. Although frequently associated with respiratory symptoms, many DLAs are found incidentally on chest imaging. Recognition of unique radiological findings of DLAs can avoid unnecessary and costly investigative tests. Management for symptomatic lesions is always surgical resection if possible.